Effects of unilateral and bilateral plyometric training on power and jumping ability in women - Makaruk, H.; Winchester, J. B.; Sadowski, J.; Czaplicki, A.; Sacewicz, T. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the effects of unilateral and bilateral plyometric exercise on peak power and jumping performance during different stages of a 12-week training and detraining in women. Forty-nine untrained but physically active female college students were randomly assigned to 1 of 3 groups: unilateral plyometric group (n = 16), bilateral plyometric group (BLE; n = 18), and a control group (n = 15). Peak power and jumping ability were assessed by means of the alternate leg tests (10-second Wingate test and 5 alternate leg bounds), bilateral leg test (countermovement jump [CMJ]) and unilateral leg test (unilateral CMJ). Performance indicators were measured pretraining, midtraining, posttraining, and detraining. Differences between dependent variables were assessed with a 3 × 4 (group × time) repeated analysis of variance with Tukey's post hoc test applied where appropriate. Effect size was calculated to determine the magnitude of significant differences between the researched parameters. Only the unilateral plyometric training produced significant (p < 0.05) improvement in all tests from pretraining to midtraining, but there was no significant (p < 0.05) increase in performance indicators from midtraining to posttraining. The BLE group significantly (p < 0.05) improved in all tests from pretraining to posttraining and did not significantly (p > 0.05) decrease power and jumping ability in all tests during detraining. These results suggest that unilateral plyometric exercises produce power and jumping performance during a shorter period when compared to bilateral plyometric exercises but achieved performance gains last longer after bilateral plyometric training. Practitioners should consider the inclusion of both unilateral and bilateral modes of plyometric exercise to elicit rapid improvements and guard against detraining.